First molecules to reactivate RASG12V GTPase activity - Aneta Wlodarczyk; Cezary Treda; Marcin Pacholczyk; Adrianna Rutkowska; Marta Wegierska; Amelia Kierasinska-Kalka; Katarzyna Wasiak; Damian Ciunowicz; Dagmara Grot; Pawel Glowacki; Ewelina Stoczynska-Fidelus; Piotr Rieske (BMC Cancer)
Abstract Background Small-molecule compounds that even partially restore the GTPase activity of RASG12V can be used in anticancer therapy. Until now, attempts to obtain such compounds have failed. Compounds with this ability have been defined in our research. Methods The compounds were initially identified through virtual screening, and their optimal binding conformation in the RAS SW-II pocket was determined using the flexible docking technique. Efficacy was verified based on the IC50 determination, GTPase activity, as well as the AKT and ERK phospho WB assays. Results The IC50 of the tested compounds was significantly lower against cells with the RASG12V mutation than against selected types of normal cells. The molecular mechanism of action of these compounds was proposed – minimization of the negative impact of the V12 sidechain on GTP hydrolysis of RASG12V. The work also indicates that the model of action of RAS mutants in cell lines is incomplete. The analysed cell line (SW-480) with RAS mutations does not always show increased ERK and AKT activity. Conclusions We have demonstrated molecules that partially restore the GTPase activity of RASG12V. Their mechanism of action is well explained based on current RAS mutant conformation and mechanistic models. These molecules inhibit the RAS-AKT pathway and show higher cytotoxicity against cancer cells with the RASG12V mutation (SW-480 cell line). However, SW-480 cells can switch into the subline proliferating independently of AKT phosphorylation and show partial resistance to the molecules described in this article.